Correlation of serum and local CXCL13 levels with disease severity in patients with non-traumatic osteonecrosis of femoral head - Yong-Heng Zhao; Wen-Xiu Zhu; Qing-He Ye; Peng Zhang; Biao-Fang Wei (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Objective The primary aim of the present study was to explore the potential correlation of serum / local CXCL13 expressions and disease severity in non-traumatic osteonecrosis of the femoral head (NT-ONFH). Methods In total, NT-ONFH patients (n = 130) together with healthy controls (HCs, n = 130) were included in this investigation. Radiographic progression was evaluated based on the imaging criteria outlined in the ARCO classification system. To assess the diagnostic value of serum CXCL13 in relation to radiographic progression, Receiver operating characteristic (ROC) curve analysis was conducted. Serum CXCL13 levels were quantified utilizing ELISA in all participants. Furthermore, local protein/mRNA expressions of CXCL13 were examined employing immunohistochemistry, western blot, as well as RT-PCR techniques. Clinical severity was appraised using the visual analogue scale (VAS), Harris Hip Score (HHS), and Western Ontario as well as McMaster Universities Osteoarthritis Index (WOMAC). Results The findings revealed a significant reduction in serum CXCL13 levels among NT-ONFH patients in contrast with HCs. Moreover, both mRNA and protein expressions of CXCL13 were markedly decreased in the necrotic area (NA) than the non-necrotic area (NNA) as well as the healthy femoral head tissues. Additionally, serum CXCL13 levels were substantially lower among patients classified as ARCO stage 4 than those at ARCO stage 3. The concentrations of CXCL13 in stage 3 patients were notably diminished relative to those at ARCO stage 2. Notably, serum CXCL13 levels demonstrated a negative association with ARCO grade. Furthermore, these levels were also inversely linked to VAS scores as well as WOMAC scores while displaying a positive association with HHS scores. The findings of ROC curve suggested that reduced serum CXCL13 levels could be an underlying indicator for ARCO stage. Conclusions The reduced levels of either serum CXCL13 or local CXCL13 were intricately linked to disease severity for patients with NT-ONFH.